A general model for predicting the off-axis performance of fiber reinforced composite materials. (December 2021) - Li, Hao; Wei, Yang; Wang, Libin
Abstract: To better characterize the off-axis performance of fiber reinforced composite materials, a general model is developed in this paper. One coefficient was added to this model to help control the shape, and it could be calculated by corresponding off-axis performance data at any angle. After demonstrating the influence of the coefficients and material anisotropic characteristics on the shape for the proposed model, the collected off-axis performance data of fiber reinforced composite materials (e.g., wood, engineered bamboo products, and fiber/epoxy composites) were used for proving the validity of the model. Furthermore, three optimization methods were presented to improve the accuracy of the model to allow for material characteristics and measurement errors. The results showed that the general model could accurately capture the off-axis performance characteristics of anisotropic fiber reinforced composite materials.